2018
DOI: 10.1016/j.yjmcc.2018.04.011
|View full text |Cite
|
Sign up to set email alerts
|

HDAC inhibition helps post-MI healing by modulating macrophage polarization

Abstract: Inhibition of HDAC activity result in the early recruitment of reparative CD45/CD11b/CD206 macrophages in the post-MI heart and correlates with improved ventricular function and remodeling. This work identifies a very promising therapeutic opportunity to manage macrophage phenotype and enhance resolution of inflammation in the post-MI heart.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
31
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 45 publications
0
31
0
Order By: Relevance
“…To correlate our in vitro analysis in BMDCs, showing that IGF1 induced CD206 + M2-like macrophage polarization, we used CD206 as a marker to identify reparative macrophages. 17 As shown in Figure 6B, treatment did not significantly affect the number of leukocytes (CD45 + ), neutrophils (CD11b + Ly6G + ), and macrophages (CD11b + Ly6G À F4/80 hi CD64 + ). However, analysis of macrophage subtypes showed that IGF1 substantially increased the mean number of CD206 + macrophages (152,777 ± 13,510 versus 108,071 ± 14,023, p = 0.041) without affecting the number of CD206 À macrophages.…”
Section: Igf1 Treatment Increases Cd206 + Macrophages In Cardiac Tissmentioning
confidence: 74%
“…To correlate our in vitro analysis in BMDCs, showing that IGF1 induced CD206 + M2-like macrophage polarization, we used CD206 as a marker to identify reparative macrophages. 17 As shown in Figure 6B, treatment did not significantly affect the number of leukocytes (CD45 + ), neutrophils (CD11b + Ly6G + ), and macrophages (CD11b + Ly6G À F4/80 hi CD64 + ). However, analysis of macrophage subtypes showed that IGF1 substantially increased the mean number of CD206 + macrophages (152,777 ± 13,510 versus 108,071 ± 14,023, p = 0.041) without affecting the number of CD206 À macrophages.…”
Section: Igf1 Treatment Increases Cd206 + Macrophages In Cardiac Tissmentioning
confidence: 74%
“…This study identifies LAIR1 as a promising therapeutic target in atherosclerosis and related disorders. Another study demonstrated the involvement of histone deacetylases (HDAC) in the early recruitment of reparative CD45+/CD11b+/CD206+ macrophages to the heart after myocardial infarction and its positive correlation with the ventricular function and remodeling [ 30 ]. A study by Cao et al demonstrates that in the histone deacetylase 9 knockout mice ( Hdac9 -/- ), macrophages are inclined towards M2 phenotypes and show decreased expression of the pro-inflammatory M1 markers [ 31 ].…”
Section: Macrophages As Perfect Cells For Reprogrammingmentioning
confidence: 99%
“…However, it should be noted that gene expression and molecular marker distribution changes induced in cultured macrophages are indeed biased toward a “classical” or “alternative” activation state as described by M1 and M2 [also suggested to be replaced by terms denoting the polarization stimulus, e.g., M(IL4) and M(IFN-γ) (132)]. Although these may not coincide to the in vivo states, some markers and cytokines are still used to describe polarization and the paradigm has not been fully abandoned in the literature, including the characterization of cardiac pathology [e.g., (136, 137)]. Interestingly, macrophages can also mimic other cardiac cell types.…”
Section: Cardiac Subpopulations and The Contribution Of Innate Immunitymentioning
confidence: 99%